Estrutura da comunidade de copépodes (Crustacea, Copepoda) em área de reservatório com atividade de piscicultura em tanques-rede - Tibúrcio, Vanessa Graciele (2014)
Considering the importance of water resources for regional social and economic development, according to the multiple uses associated with human activities, it is relevant to the proper use and management of freshwater ecosystems. Accordingly, we investigated the variation of environmental variables and their influence on the community structure of copepods in the reservoir area of activity with fish farming in cages in temporal and spatial scale. The study area was the Rosana Reservoir, Crow River, a tributary of Paranapanema River (PR/SP). Three sets of cages with different stocking densities of tilapia were installed for 120 days. The first sampling was before the installation of tanks and five sampling points (treatment, two distances upstream and two downstream distances). After installing them seven points (three treatments, two distances upstream and two downstream distances) were sampled. Concomitantly sampling zooplankton, some physical and chemical parameters were measured and chlorophyll-a and nutrients. It was observed in the concentration of most nutrients (total nitrogen, nitrate, ammonium and total phosphorus) and some variables as alkalinity, conductivity and dissolved oxygen over time and study sites as well as the concentration of chlorophyll-a after installation locations in the tanks. It was observed that most of the analyzed attributes copepods community been altered over time and space studied. Therefore, considering the spatial and temporal differences , this study indicated changes in the structure of the copepod community and limnological variables , caused by the increased activity of fish farming in cages.